Reproductive Characteristics Differed in a Series of B-Congenic Lines of White Leghorns Evidently Indicating Significant Influence of Major Histocompatibility Complex in Chickens - Wang, Chong; Kulkarni, Gururaj; Zhang , Huanmin (International Journal of Poultry Science, 2015)
Reproductive characteristics were compared between a series of seven B-congenic lines of White Leghorns retrospectively using eight year’s reproduction records. The records encompass a total of 33,010 fertile eggs set to hatch under controlled conditions, which were collected accumulatively from 2,129 young hens on the USDA-ARS, Avian Disease and Oncology Laboratory specific pathogen free farm during the years (2008-2015). Over the eight year period, average fertility, embryo mortality and hatchability of fertile eggs ranged from 71.6±0.77 (line 15.N-21) to 88.2±0.56 (line 15.P-19), 18.6±0.83 (line 15.6-2) to 28.5±0.84 (line 15.N-21) and 41.2±0.92 (line 15.N-21) to 57.6±1.09 (line 15.6-2) between the B-congenic lines and from 73.0±0.93 (2014) to 87.2±0.58 (2011), 19.5±0.84 (2012) to 35.2±0.97 (2009) and 38.3±1.02 (2009) to 55.4±1.12 (2014) between the years, respectively. Statistical analyses showed both B-congenic line (genetics) and the year of line reproduction (environmental) as well as the line by year (genetics by environment) interaction significantly influenced the reproductive characteristics (p<0.0001). Considerable variation observed between the B-congenic lines each year suggests the reproductive performance followed a polygenic model of inheritance, which are attributable to genes of the major histocompatibility complex (MHC) loci. Findings from this study document the reproductive characteristics of the 7 B-congenic lines of White Leghorns and add to the mounting evidence that MHC affects reproductive characteristics in a diverse species including human, wild chimpanzees, fish, bovine, swine, mice, rats and chickens.